Mode Switching Research of Dual Redundant Electromechanical Servo System Driven by Differential - Ting Liu; Guoping Zhao; Yufeng He; Zhiyuan Yu; Yuping Huang (Jixie chuandong, 2022)
In order to study the mode switching and fault reconfiguration of the 10 kW dual redundancy electromechanical servo system driven by differential when one channel fault occurs， through simulation analysis， the system parameters of transient response and frequency characteristic under the active- active working mode are compared with those under the active-standby working mode. The sinusoidal switching process of the active-active switching and active-standby switching are analyzed. The sinusoidal variation curves of the active-active switching mode and the active-standby switching mode are carried out by the test rig. Simulation comparison shows that， comparison with the active-standby working mode， it is found that the active-active working mode possesses better parameters of transient response and frequency characteristic. Consistent with simulation， the test shows that the switching time and oscillation process of switching at the zero point are longer and non-smoother than those of switching at the maximum displacement point. For the 10 kW electromechanical servo system with only internal friction and inertia load， either switching mode can be switched reliably.